Resonance heat transfer during the forced convection of the Al2O3 nanofluid in a horizontal channel with a heat sink - Bouttout, Abdelouahab (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: The continuous advancements in electronic device technologies have led to increased power densities, resulting in substantial heat generation during their operation. Efficient thermal management is essential to maintain optimal performance, prolong device lifespan, and prevent thermal-induced failures. Traditional cooling methods, such as air and liquid cooling, have reached their limitations in meeting the escalating cooling demands. Consequently, the implementation of nanofluids as a novel cooling medium has gained significant attention in recent years.Methods: The current study aims to determine the wide band of the frequencies for which the heat transfer is maximal during the cooling of nine electronic components mounted on a horizontal channel using the Al2O3 nanofluid. This phenomenon is called resonance heat transfer, and it occurs when the frequency of external forcing (pulsation or oscillation) matches the natural frequency of the convective flow of the nanofluid. The finite volume method has been used to solve the governing equation. Two cases are considered in this work: uniform and pulsed inlet flow. The electronic components have been considered as heated blocks with the same space between them.Results: The results show that the flow is unstable for the critical Reynolds number Re≈2000 Al2O3 nanofluid with frequency as the Strouhal number St=1.2 and a fraction concentration of 0.10. It corresponds to a flow velocity of 0.211 m/s and a dominant frequency of fr=34 Hz.Conclusions: The enhanced heat transfer is calculated as the rate of Nusselt number of pulsation flow with the Nusselt number of uniform flow. An enhanced heat transfer rate can be achieved 30-170 % within a band of the Strouhal number St=[0.2-1.2] corresponding to a band of frequency fr =[12-34] Hz.
Keywords: nanofluid; resonance; heat transfer; heat sink; convection; Strouhal number